Pengaruh Problem Based Instruction terhadap Pemahaman Penggunaan Alat Pelindung Diri Kapal Niaga pada Siswa SMK - Jamilul Hakam; Nyoman Ardiana Listriyawati; Kuncowati Kuncowati (Politeknik bumi Akpelni, 2026)
Based on the low student learning outcomes with these conditions influenced by the learning process which is still dominated by lecture methods and does not involve students in analyzing real problems related to work safety. In fact, understanding the use of PPE is an important aspect in preventing work accidents on merchant ships. This study aims to determine the effect of the PBI learning model on the understanding of the use of personal protective equipment. This type of research uses research (Pre-Experimental) with a quantitative descriptive approach with a focus on providing treatment related to learning the application of personal protective equipment, for experimental research it can be explained that this type of research is used to find the effect of the treatment given to the subject. The results of the study on the descriptive test show the average value on multiple choice and essay questions shows there is a positive impact on the pre-test data of 35.14 and post-test 43.00, while on the essay question data for the pre-test 50.78 and post-test 66.70. In the regression test to see the impact of providing the Problem Based Instruction learning model on multiple choice questions with a sig value of 0.019 <0.05 while the results of the essay question test show a sig value of 0.021 > 0.05). The conclusion of this study shows that the Problem Based Instruction learning model is effective in understanding the procedures for using personal protective equipment for students at Sunan Drajat Vocational School.